2017
DOI: 10.1007/s10620-017-4600-4
|View full text |Cite
|
Sign up to set email alerts
|

FFA3 Activation Stimulates Duodenal Bicarbonate Secretion and Prevents NSAID-Induced Enteropathy via the GLP-2 Pathway in Rats

Abstract: Therapy with nonsteroidal anti-inflammatory drugs (NSAIDs) is associated with enteropathy in humans and experimental animals, a cause of considerable morbidity. Unlike foregut NSAID-associated mucosal lesions, most treatments for this condition are of little efficacy. We propose that the endogenously-released intestinotrophic hormone glucagon-like peptide-2 (GLP-2) prevents the development of NSAID-induced enteropathy. Since the short-chain fatty acid (SCFA) receptor FFA3 is expressed on enteroendocrine L cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
(68 reference statements)
2
15
0
Order By: Relevance
“…We recently reported that the rat proximal duodenum possesses an active short-chain fatty acid (SCFA) absorption mechanism and that luminal SCFAs stimulate duodenal bicarbonate secretion via SCFA receptors (FFA2 and FFA3) and SCFA transporter-dependent pathways (Figure 2) [65;66]. Luminal SCFA acetate increases the secretory rate of bicarbonate through FFA2-mediated 5-HT release and FFA3-mediated GLP-2 release, consistent with results of studies in which selective FFA agonists were used singly [23;67*]. Since the response to acetate is significantly reduced by SCFA transporter inhibition or by capsaicin deafferentation [66], afferent nerves may detect SCFA directly after absorption and potentiate EEC transmitter release to increase duodenal mucosal protection.…”
Section: Tuft Cellssupporting
confidence: 76%
“…We recently reported that the rat proximal duodenum possesses an active short-chain fatty acid (SCFA) absorption mechanism and that luminal SCFAs stimulate duodenal bicarbonate secretion via SCFA receptors (FFA2 and FFA3) and SCFA transporter-dependent pathways (Figure 2) [65;66]. Luminal SCFA acetate increases the secretory rate of bicarbonate through FFA2-mediated 5-HT release and FFA3-mediated GLP-2 release, consistent with results of studies in which selective FFA agonists were used singly [23;67*]. Since the response to acetate is significantly reduced by SCFA transporter inhibition or by capsaicin deafferentation [66], afferent nerves may detect SCFA directly after absorption and potentiate EEC transmitter release to increase duodenal mucosal protection.…”
Section: Tuft Cellssupporting
confidence: 76%
“…These observations, repeated many times, have been mostly unexplained, but more recently data have emerged that these changes are likely due to the production of bacterial fermentative metabolites, in particular short-chain fatty acids (SCFAs), by the gut microbiota [24][25][26]. Since L cells express the G-proteincoupled receptors (GPCR), GPR 41 and 43 also termed free fatty acid (FFA)3 and FFA2, and since L cells in rats release GLP-2 into the portal vein in response to luminal perfusion with FFA3 ligands [27], it is likely that microbial fermentation products such as SCFAs release GLP-2 from L cells, increasing the rate of epithelial proliferation [27,28], helping to explain the effects of high-fiber diets and starvation on the rate of intestinal proliferation.…”
Section: -Graham Greene the End Of The Affairmentioning
confidence: 99%
“…These results suggest that exogenous GLP-2 or luminal nutrients that enhance endogenous GLP-2 release combined with DPP4 inhibition may be therapeutic for NSAID-induced enteropathy. Furthermore, oral administration of AR420626 prevents the formation of NSAID-induced small intestinal ulcers [8]. FFA3 is also expressed on myenteric neurons.…”
Section: Ffa3-glp-2 and Nonsteroidal Anti-inflammatory Drug (Nsaid)-imentioning
confidence: 99%
“…DPP4 inhibitors are clinically used to treat diabetes, since DPP4 inhibition enhances the insulinotropic effect of GLP-1 [33]. The DPP4 inhibitor NVP-728 enhances amino acid-and bile acid-augmented HCO 3 − secretion in rat duodenum via prolonging the t 1/2 of GLP-2 [34], suggesting that enhanced endogenous GLP-2 signaling by the luminal GPCR agonist such as amino acids, bile acids, and FFA3 ligands [8,34], acting at L cells, combined with DPP4 inhibition augments duodenal defense mechanisms.…”
Section: Ffa3-glp-2 and Nonsteroidal Anti-inflammatory Drug (Nsaid)-imentioning
confidence: 99%
See 1 more Smart Citation